The Reality of Field Training for Media Students in Saudi Universities: Application to Hail University Media Students (2023-2024) (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to ascertain the reality of field training for media students in Saudi universities by applying it to students in the Department of Media at the College of Arts (University of Hail). The goal is to provide suggestions and solve the problems of students' inadequate training dosages in media institutions and the absence of clear educational plans and programs. The study brought up some significant questions, I attempted to address in the applied study. It employed analytical and descriptive methodology solutions that might help address the challenges and issues encountered during the field training process, the study's weakness of interest is its main issue.  A questionnaire sheet served as the primary research instrument and was used to survey practice methods. The most significant findings from the study's conclusion were that various schools and departments of media at universities do not exist and that training, practice, and practical application are more crucial to media as a science than theoretical study. It is a fact that field training in the Department of Media at Hail University requires more work, review, and follow-up, some colleges and university media departments lack the infrastructure necessary to qualify and train students. Additionally, the training doses that students receive are insufficient because they are conducted during the eighth academic credit. The study's findings included several recommendations, the most significant of which are as follows: Plans for training students and preparing them both academically and practically must be transparent and well-considered. It is necessary to take field training more seriously and to address many of the issues and challenges that students face both inside and externally. It is necessary to create coordination relationships and partnerships with various media institutions, especially outside Hail region, to benefit from them. Finally, it is necessary to strive seriously to provide internal training aids at the college. By connecting the academic theoretical part with the practical, applied aspect, editing rooms, labs, and studios can be established to train students internally, giving them greater and ongoing benefits.
Keywords: Reality; Field Training; Media Students; Hail University